THE IMPACT OF RAD6 EXPRESSION ON CHEMORESISTANT OVARIAN CANCER: A SYSTEMATIC REVIEW - Vernadesly, Leo; Nita Hertati; Pariyana (Fakultas Kedokteran Universitas Sriwijaya, 2025)
Chemotherapy is one of the modalities for treating ovarian cancer (OC), which is one of the most common reproductive organ cancers in women worldwide. Overexpression of RAD6 has been identified as a significant factor in chemoresistance in ovarian cancer patients. This systematic review aims to evaluate the relationship between RAD6 overexpression and chemoresistance in ovarian cancer. The databases used include PubMed, ProQuest, Science Direct, and Google Scholar, focusing on articles from the last 10 years. Out of 162 articles retrieved, only 4 met the selection criteria and were used in the analysis. The analysis results indicate that RAD6 overexpression is closely associated with increased resistance to chemotherapeutic agents, particularly platinum. The underlying mechanisms include enhanced DNA damage tolerance, increased proliferation, invasion, and the ability of cancer cells to develop stem-like phenotypes. These findings highlight RAD6 as a potential therapeutic target in preventing chemoresistance in OC. Further research is needed to develop specific RAD6 inhibitors that can be used in combination with conventional chemotherapy to improve treatment response and patient prognosis.